Productivity changes in the Mediterranean Sea drive foraging movements of yelkouan shearwater Puffinus yelkouan from the core of its global breeding range. (29th June 2021) - Pezzo, Francesco; Zenatello, Marco; Cerritelli, Giulia; Navone, Augusto; Giunchi, Dimitri; Spano, Giovanna; Pollonara, Enrica; Massolo, Alessandro; Gagliardo, Anna; Baccetti, Nicola
Abstract: Pelagic seabirds are tied to their breeding colonies throughout their long‐lasting breeding season, but at the same time, they have to feed in a highly dynamic marine environment where prey abundance and availability rapidly change across space and seasons. Here, we describe the foraging movements of yelkouan shearwater Puffinus yelkouan, a seabird endemic to the Mediterranean Sea that spends its entire life cycle within this enclosed basin and whose future conservation is intimately linked to human‐driven and climatic changes affecting the sea. The aim was to understand the main factors underlying the choice of foraging locations during the reproductive phases. A total of 34 foraging trips were obtained from 21 breeding adults tagged and tracked on Tavolara Archipelago (N Sardinia, Italy). This is the largest and most important breeding area for the species, accounting for more than 50% of the world population. The relationships between foraging movements during two different breeding stages and the seasonal changes of primary productivity at sea were modeled. Movements appeared to be addressed toward inshore (<20 km), highly productive, and relatively shallow (<200 m) foraging areas, often in front of river mouths and at great distances from the colony. During incubation, the Bonifacio Strait and other coastal areas close to North and West Sardinia were the most preferred locations (up to 247 km from the colony). During the chick‐rearing phase, some individuals reached areas placed at greater distances from the colony (up to 579 km), aiming at food‐rich hotspots placed as far north as the Gulf of Lion (France). The need for such long distance and long‐lasting foraging trips is hypothesized to be related to unfavorable conditions on the less productive (and already depleted) Sardinian waters.